Influence of type and amount of organic matters on the iron sorption of acid mine drainage onto reclaimed-mining soils - Akhmad Rizalli Saidy; Bambang Joko Priatmadi; Meldia Septiana (Journal of Degraded and Mining Lands Management, 2021)
Mining activity may potentially produce acid mine drainage (AMD), which has relatively high acidity and dissolved heavy metal concentrations. Constructed wetlands is one of the AMD management methods in which organic matter (OM) plays a very important function in reducing the concentration of heavy metals in AMD through absorption and precipitation processes. Three types of OM (empty fruit bunches of oil palm, chicken manure and water hyacinth) and five levels of OM (0, 10, 20, 30 and 40 Mg ha-1) were applied to reclaimed-mining soils (RMS) in an incubation study. A batch experiment was then performed to measure the effect of OM application on the maximum sorption capacity (Qmax) of iron (Fe) from the AMD onto the mixed soil-OM. The application of OM resulted in increases in soil pH, carboxylic groups, and total functional groups, in which these increases varied based on the types and amounts of OM application. This study also revealed that OM application resulted in increasing Fe sorption. The application of OM increased Qmax values from 2077 to 2348-3259 mg kg-1 (water hyacinth), to 2607-3635 mg kg-1 (chicken manure), and to 2219-2992 mg kg-1 (empty fruit bunches of oil palm). Increasing these Qmax values may ascribe to increasing functional groups of the RMS with OM application. The results prove the importance of OM in controlling the sorption of Fe from AMD onto soils.